Dynamic Games in Economics - Haunschmied, Josef; Veliov, Vladimir M.; Wrzaczek, Stefan; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2014)
Dynamic game theory serves the purpose of including strategic interaction in decision making and is therefore often applied to economic problems. This book presents the state-of-the-art and directions for future research in dynamic game theory related to economics. It was initiated by contributors to the 12th Viennese Workshop on Optimal Control, Dynamic Games and Nonlinear Dynamics and combines a selection of papers from the workshop with invited papers of high quality.
Robust Markov Perfect Equilibria in a Dynamic Choice Model with Quasi-hyperbolic Discounting -- Stochastic Differential Games and Intricacy of Information Structures -- Policy Interactions in a Monetary Union: An Application of the OPTGAME Algorithm -- The Dynamics of Lobbying Under Uncertainty: On Political Liberalization in Arab Countries -- A Feedback Stackelberg Game of Cooperative Advertising in a Durable Goods Oligopoly -- Strategies of Foreign Direct Investment in the Presence of Technological Spillovers -- Differential Games and Environmental Economics -- Capacity Accumulation Games with Technology Constraints -- Dynamic Analysis of an Electoral Campaign -- Multi-Agent Optimal Control Problems and Variational Inequality Based Reformulations -- Time-consistent Equilibria in a Differential Game Model with Time Inconsistent Preferences and Partial Cooperation -- Interactions Between Fiscal and Monetary Authorities in a Three-Country New-Keynesian Model of a Monetary Union -- Subgame Consistent Cooperative Provision of Public Goods Under Accumulation and Payoff Uncertainties.
Keywords: Economics; Mathematics; Economics, Mathematical; Operations research; Economics/Management Science; Game Theory/Mathematical Methods; Game Theory, Economics, Social and Behav. Sciences; Operation Research/Decision Theory; Operations Research, Management Science; Economic Theory